K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 6 2015

x3+4x2-3x-18=x3-2x2+6x2-12x+9x-18=x2(x-2)+6x(x-2)+9(x-2)=(x-2)(x2+6x+9)=(x-2)(x+3)2

Vì x >=2 => x3+4x2-3x-18 >=0

c: (3x-2)(x+3)<0

=>x+3>0 và 3x-2<0

=>-3<x<2/3

d: \(\dfrac{x-2}{x-10}>=0\)

=>x-10>0 hoặc x-2<=0

=>x>10 hoặc x<=2

e: \(3x^2+7x+4< 0\)

\(\Leftrightarrow3x^2+3x+4x+4< 0\)

=>(x+1)(3x+4)<0

=>-4/3<x<-1

16 tháng 7 2021

| 2-4x | = 4x-2

<=> \(\orbr{\begin{cases}\left|2-4x\right|=-2+4x=4x-2\\\left|2-4x\right|=2-4x=4x-2\end{cases}}\)

<=>\(\orbr{\begin{cases}-2+4x=4x-2\\2-4x=4x-2\end{cases}}\)

<=>\(\orbr{\begin{cases}-2+4x-4x+2=0\\2-4x-4x+2=0\end{cases}}\)

<=>\(\orbr{\begin{cases}0=0\\-8x+4=0\end{cases}}\)

<=> x=\(\frac{-4}{-8}=\frac{1}{2}\)

=> \(S=\left\{\frac{1}{2};\infty\right\}\)

2x-7> 3(x-1)

<=>2x-7>3x-3

<=>2x-3x>-3+7

<=>-x>4

<=>x<4

=>S={x/x<4}

1-2x<4(3x-2)

<=>1-2x<12x-8

<=>-2x-12x<-8-1

<=>-14x<-9

<=>x>\(\frac{9}{14}\)

=>S={\(\frac{9}{14}\)}

-3x+2|-4 -x|> 0

<=>\(\orbr{\begin{cases}-3x+2+4+x>0\\-3x+2-4x-x>0\end{cases}}\)

<=>\(\orbr{\begin{cases}-2x+6>0\\-8x+2>0\end{cases}}\)

<=>\(\orbr{\begin{cases}-2x>-6\\-8x>-2\end{cases}}\)

<=>\(\orbr{\begin{cases}x< 3\\x< \frac{1}{4}\end{cases}}\)

=>S={x/x<3;x/x<\(\frac{1}{4}\)}

4x-1|x-2|< 0

<=>\(\orbr{\begin{cases}4x-1-x+2< 0\\4x-1+x-2< 0\end{cases}}\)

<=>\(\orbr{\begin{cases}3x+1< 0\\3x-3< 0\end{cases}}\)

<=>\(\orbr{\begin{cases}3x< -1\\3x< 3\end{cases}}\)

<=>\(\orbr{\begin{cases}x< \frac{-1}{3}\\x< 1\end{cases}}\)

=>S={x/x<\(\frac{-1}{3}\);x/x<1}

27 tháng 4 2017

a) x2-3x-x+3>0

<=> x(x-3)-(x-3)>0

<=> (x-3)(x-1)>0

\(\left[{}\begin{matrix}\left\{{}\begin{matrix}x-3>0\\x-1>0\end{matrix}\right.\\\left\{{}\begin{matrix}x-3< 0\\x-1< 0\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x>3\\x>1\end{matrix}\right.\\\left\{{}\begin{matrix}x< 3\\x< 1\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x>3\\x< 1\end{matrix}\right.\)

27 tháng 4 2017

b) x3-2x2+3x-2\(\ge\) 0

<=> x3-x2-x2+x+2x-2\(\ge0\)

<=> (x-1)(x2-x+2)\(\ge0\)

Vì x2-x+2\(\ge0\)

nên x-1\(\ge0\)

x>=1